2020
DOI: 10.1242/dev.175786
|View full text |Cite
|
Sign up to set email alerts
|

Transposable elements, circular RNAs and mitochondrial transcription in age-related genomic regulation

Abstract: Our understanding of the molecular regulation of aging and age-related diseases is still in its infancy, requiring in-depth characterization of the molecular landscape shaping these complex phenotypes. Emerging classes of molecules with promise as aging modulators include transposable elements, circRNAs and the mitochondrial transcriptome. Analytical complexity means that these molecules are often overlooked, even though they exhibit strong associations with aging and, in some cases, may directly contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 261 publications
(311 reference statements)
3
26
0
Order By: Relevance
“…These pathways, which represent both adaptive and maladaptive cellular responses, refer to a series of genes related to glycolysis for energy production, antioxidant and redox regulatory systems, autophagy/mitophagy, apoptosis, chromatin remodelling, and compartment-specific unfolded protein stress response. In this context, nuclear mRNAs or non-coding RNAs of either nuclear or mitochondrial origin, such as processed mt-tRNA fragments exported to the cytoplasm or circular RNAs [ 40 , 42 , 43 , 44 ], may represent possible targets of cytosolic RNA-binding proteins for regulation of nuclear gene expression. In addition to mitochondrial retrograde signalling to the cytoplasm, the full recovery of cell viability might be the result of Cterm capacity to bind cytosolic RNA targets.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways, which represent both adaptive and maladaptive cellular responses, refer to a series of genes related to glycolysis for energy production, antioxidant and redox regulatory systems, autophagy/mitophagy, apoptosis, chromatin remodelling, and compartment-specific unfolded protein stress response. In this context, nuclear mRNAs or non-coding RNAs of either nuclear or mitochondrial origin, such as processed mt-tRNA fragments exported to the cytoplasm or circular RNAs [ 40 , 42 , 43 , 44 ], may represent possible targets of cytosolic RNA-binding proteins for regulation of nuclear gene expression. In addition to mitochondrial retrograde signalling to the cytoplasm, the full recovery of cell viability might be the result of Cterm capacity to bind cytosolic RNA targets.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other non-coding RNAs appear to act as epigenetic regulators. For instance, there is a growing body of evidence suggesting that small interfering RNAs (siRNAs), small nucleolar RNAs (snoRNAs), circular RNAs (circRNAs), piwi-interacting RNAs (piRNAs), or long non-coding (lncRNAs) have a pivotal role in the epigenetic landscape (reviewed elsewhere [ 100 , 101 , 102 ]). However, the direct relationship between these non-coding RNAs and nutrition still remains unknown.…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Furthermore, TE recombination events are associated with early-onset PD. Bravo et al, (2018) reported five structural variations in the PRKN gene, which is the most frequently mutated gene in this condition, including deletions and exon rearrangements, all of which were caused by recombinatory events triggered by TE reactivation [ 83 ]. It was also reported that pathogenic Tau protein leads to a decrease in piRNA-mediated regulation, which increases TE retrotransposition in PD neurons, triggering oxidative stress and cell death [ 84 , 85 ].…”
Section: Genetic Alterations In Parkinson’s Diseasementioning
confidence: 99%